Viral enteritis in intestinal transplant recipients. Issue 2 (29th January 2020) - Servais, Abigail M.; Keck, Megan; Leick, Mary; Mercer, David F.; Langnas, Alan N.; Grant, Wendy J.; Vargas, Luciano M.; Merani, Shaheed; Florescu, Diana F.
Abstract: Intestinal transplant recipients (ITR) are at high risk for infections due to the high level of immunosuppression required to prevent rejection. There are limited data regarding viral enteritis post‐intestinal transplantation. We retrospectively reviewed ITR transplanted between January 2008 and December 2016. Descriptive statistics, including mean (standard deviation) and median (range), were performed. Sixty‐one (43.9%) of the 139 transplanted patients had viral enteritis: 26% norovirus, 25% adenovirus, and 9% each rotavirus and sapovirus. The median age of pediatric patients was 1.6 years (0.4‐16.9) and for adults 36.3 years (27.1‐48.2). Fifty‐seven (58%) of 99 pediatric ITR had viral enteritis compared to 4 (10%) of 40 adult ITR. Median time‐to‐clinical resolution of enteritis for all patients was 5 days (1‐92). Standard of care therapies administered: anti‐motility agents (10%), anti‐emetics agents (14%), and intravenous fluids (42%). There was a higher incidence of viral enteritis in pediatric compared to adults ITR. The majority of viral enteritis episodes resolved within 1 week and were treated with supportive therapy.